Rancang Bangun Sistem Pendeteksi Kebocoran Gas Secara Portable pada Distributor Gas Rumah Tangga - Zamzak , M.Arif; Sudiarsa, I Wayan; Putra , I Dewa Putu Gede Wiyata (Jurnal Kendali Teknik dan Sains, 2023)
In this research we design and build a portable gas leak detection system for household gas distributors. The performance of the designed system is described and evaluated. The system aims to speed up the time in detecting gas leaks. System portability allows implementation and monitoring in the form of a website. System design and performance are assessed and proven effective in detecting gas leaks, providing a reliable and efficient solution for gas distributors. The method used is the conditional method where the gas leak detection system is made with Nodemcu esp8266, sensor mq6, buzzer, step-down lm2596, and led. The results obtained from testing the leak detection system explain the testing and evaluation of the gas cylinder inspection system. The system is designed to check 3kg gas cylinders, category level 1 with numbers 300-500, category level 2 with numbers 500-750, category level 3 with numbers 750-1000, and category level 4 with numbers higher than 1000. Detection of gas leaks in each valve takes about 13 seconds to detect leaking gas, send data to the website and provide output to the buzzer.